Prediction of amblyopia and squint by means of refraction at age 1 year. - Ingram, R. M. (1986)
In this series amblyopia, uncorrectable by spectacles and occlusion, was highly likely (48%) if a child had +3.50 or more dioptres of meridional hypermetropia at age 1 year. 45% of children with this refraction also had a squint. All those who remained with severely defective acuity in spite of treatment had either +3.50 or more dioptres of meridional hypermetropia or 4 or more dioptres of meridional myopia at age 1 year. These children were identifiable in the 3.7% of the population at age 1 year who showed high refractive errors. Squint as such was not so accurately predictable. Of those children with squint 71% had less than +3.50 dioptres of meridional hypermetropia at age 1 year--an incidence of 4.4% of the population. Apart from two 'congenital myopes' only 16% of these had residual amblyopia after treatment, and their last known acuity was never less than 6/12. Astigmatism in infancy or later is not significantly associated with squint or amblyopia.